One plus one [compact disc, unabridged] : a novel - Moyes, Jojo, 1969- (Penguin Audio, 2014)
Suppose your life sucks. A lot. Your husband has done a vanishing act, your teenage stepson is being bullied, and your math whiz daughter has a once-in-a-lifetime opportunity that you can't afford to pay for. That's Jess's life in a nutshell-until an unexpected knight in shining armor offers to rescue them. Only Jess's knight turns out to be Geeky Ed, the obnoxious tech millionaire whose vacation home she happens to clean. But Ed has big problems of his own.